2020
DOI: 10.3389/fcimb.2020.598938
|View full text |Cite
|
Sign up to set email alerts
|

The Lung Microbiome of Three Young Brazilian Patients With Cystic Fibrosis Colonized by Fungi

Abstract: Microbial communities infiltrate the respiratory tract of cystic fibrosis patients, where chronic colonization and infection lead to clinical decline. This report aims to provide an overview of the diversity of bacterial and fungal species from the airway secretion of three young CF patients with severe pulmonary disease. The bacterial and fungal microbiomes were investigated by culture isolation, metataxonomics, and metagenomics shotgun. Virulence factors and antibiotic resistance genes were also explored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…For instance, Exophiala spinifera ( 35 ), Nannizzia gypsea ( 36 ), Blastomyces gilchristii ( 37 ), and Wallemia mellicola ( 38 ) were related to skin infections. Also, Torulaspora delbrueckii ( 39 ), Aspergillus terreus ( 40 ), Aspergillus nomius ( 41 ), and Aspergillus fumigatus ( 42 ) were capable of disrupting host immunity and recognized as opportunistic pathogens for pulmonary infections. Previous reports indicated that Agaricus bisporus and Saccharomycopsis fibuligera had beneficial effects on human health ( 43 45 ), but these species might have adverse effects on BP regulation because of their enrichment in HTN.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Exophiala spinifera ( 35 ), Nannizzia gypsea ( 36 ), Blastomyces gilchristii ( 37 ), and Wallemia mellicola ( 38 ) were related to skin infections. Also, Torulaspora delbrueckii ( 39 ), Aspergillus terreus ( 40 ), Aspergillus nomius ( 41 ), and Aspergillus fumigatus ( 42 ) were capable of disrupting host immunity and recognized as opportunistic pathogens for pulmonary infections. Previous reports indicated that Agaricus bisporus and Saccharomycopsis fibuligera had beneficial effects on human health ( 43 45 ), but these species might have adverse effects on BP regulation because of their enrichment in HTN.…”
Section: Discussionmentioning
confidence: 99%